When the child gets in the news? A case study on the national written media in Turkey - Kuş, Zafer; Karatekin, Kadir; Öztürk, Durdane; Elvan, Özlem (Informa UK Limited, 2016)
AbstractThe main purpose of this study is to analyze news stories regarding children in the national print media in the last five years using top eight newspapers in terms of circulation and evaluate these news stories based on the Convention on the Rights of the Child, which was issued by the UN and signed by Turkey. The research was undertaken as a case study. The study data were collected from top eight newspapers in terms of circulation between 2010 and 2014 in order to reveal when and how newspapers at national level represent children and the scientific content of impressions in the national media. Results show that children appear in the national media in mostly negative cases. In conclusion, it was observed in this study, children’s rights to life, development, protection, and participation were violated at both national and international levels. In this sense, news reflects the truth about “children’s rights violations”. However, the way that children appear in news and reflection in media consti...
Keywords: 5. Gender equality; 4. Education; 10. No inequality; 16. Peace & justice